2022
DOI: 10.21603/2074-9414-2021-4-883-904
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Using Soil Microbiome of Mine Tips for Remediation of Anthropogenically Disturbed Ecosystems

Abstract: Introduction. Coal industry increases soil pollution with heavy metals and polycyclic aromatic hydrocarbons. Therefore, resoiling is an urgent problem that requires an immediate solution. The present research objective was to substantiate the use of microorganisms from mine tips in order to decrease soil pollution with heavy metals and oil compounds. Study objects and methods. The review featured five years of publications in Scopus, Web of Science, and Elibrary, which were subjected to analysis, systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Ufimtsev [167] described that the common pine Pinus sylvestris L., common sea buckthorn Hippophae rhamnoides L., and weeping birch Betula pendula Tristis are suitable for use at the regional level for reclamation. For effective land reclamation, in addition to the formation of a plant community (flora), it is necessary to maintain the ecosystem as a whole, i.e., the formation of microbiota and fauna in the territories [168,169]. It is important to use a combination of land reclamation methods to achieve a maximum result to improve the ecological situation of the region [170].…”
Section: Russian Experience In Reclamation Of Disturbed Landsmentioning
confidence: 99%
“…Ufimtsev [167] described that the common pine Pinus sylvestris L., common sea buckthorn Hippophae rhamnoides L., and weeping birch Betula pendula Tristis are suitable for use at the regional level for reclamation. For effective land reclamation, in addition to the formation of a plant community (flora), it is necessary to maintain the ecosystem as a whole, i.e., the formation of microbiota and fauna in the territories [168,169]. It is important to use a combination of land reclamation methods to achieve a maximum result to improve the ecological situation of the region [170].…”
Section: Russian Experience In Reclamation Of Disturbed Landsmentioning
confidence: 99%
“…And vice versa: in the absence of conditions for maintaining the stable vital activity of certain types of microorganisms, their development slows down, and their composition and quantity degrade. Such communities are gradually replaced by species better adapted to new conditions [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that HMs toxicity and mobility is depend on the degree of oxidation of HMs ( Haque et al., 2022 ). Microbe use HMs pollutants as a food source and change their redox potential ( Faskhutdinova et al, 2021 ). Under HMs stress, some microbes also secrete different substances including polysaccharides, proteins, and lipids that can bind HMs ions and therefore reduce their availability ( Martis et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%